Le Caire, 2011. Plongée ethnographique au coeur des lijân sha’abeya (comités populaires) - Perrine Lachenal (L’Année du Maghreb)
Tahrir Square in downtown Cairo appeared as the principal scene of the demonstrations that shook Egypt in early 2011 and drove Hosni Mubarak to step down – almost to the point of forgetting the rest of the city, an immense area which was affected during the same period by dynamics that gave rise to new phenomena, including “popular committees”. To cope with the calculated withdrawal of police and fear caused by reports – real or imagined – of urban violence, residents of Cairo got organized. First spontaneously, then more and more “professionally”, hundreds of “popular committees” or lijân sha’abeya ensured security in different neighborhoods of Cairo during more than three weeks. Through a study based on accounts by those who made up these civilian “brigades”, they appear to be unique examples of spontaneous collective organization, backings of unlikely alliances and assertions of identity – both spatial and sexual. Far from the epicenter of the revolution, in the familiar space of intimate neighborhoods and homes, other players did not attract as much media attention yet contributed in “making” history.